Experience of foreign countries in social protection of the population. Pension reforms in the cis countries - Samyeva Gulnoza Tokhirovna; Abdieva Dilshoda Oybek kyzy (THE INNOVATION ECONOMY, 2026)
This scientific article is devoted to the issues of social security and social protection of the population - a set of legal, economic and social measures that ensure social and material security of the population of the country and have developed in society. The article reflects that the main goal of social protection is to ensure a continuous improvement in the well-being of the population, eliminate sharp differences in education, culture, professional qualifications and incomes of the population, assist society in ensuring a decent standard of living for a person and his development. The article defines the main areas of social protection: ensuring free socio-economic activity; employment, choice of profession, training and education; income guarantee; ensuring the income of each citizen as a result of his economic activity; consumer protection, consumer societies; ensuring the quality of goods and services, consumer guarantees; providing medical services to the population. The article analyzes the social security system and issues of pension provision, benefits, various benefits for the needy, low-income segments of the population, as well as foreign experience and practice of their implementation